2015
DOI: 10.1016/j.psyneuen.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative stress pathophysiology in schizophrenia as indexed by allostatic load

Abstract: Background The etiopathophysiology of schizophrenia has long been linked to stress and the influence of stress is important in all stages of the illness. Previous examinations of perceived stress and acute stress responses may not capture this longitudinal stress pathophysiology. We hypothesized that the cumulative negative effects of stress, indexed by allostatic load (AL), would be elevated in schizophrenia, and that the AL paradigm would be relevant to our understanding of pathophysiology in schizophrenia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 79 publications
(90 reference statements)
4
30
1
Order By: Relevance
“…The allostatic load concept models allostatic load as a measure of cumulative physiologic wear and tear. Although few studies have explored the relationship between subjective measures of acute stress and allostatic load, the lack of a strong correlation between measures of acute stress and AL is unsurprising and consistent with the conceptual model [1, 3, 36]. Thus, the AL model is positively correlated with chronic stressors, such as low socioeconomic status or poor sleep quality, but not acute stressors.…”
Section: Discussionmentioning
confidence: 85%
“…The allostatic load concept models allostatic load as a measure of cumulative physiologic wear and tear. Although few studies have explored the relationship between subjective measures of acute stress and allostatic load, the lack of a strong correlation between measures of acute stress and AL is unsurprising and consistent with the conceptual model [1, 3, 36]. Thus, the AL model is positively correlated with chronic stressors, such as low socioeconomic status or poor sleep quality, but not acute stressors.…”
Section: Discussionmentioning
confidence: 85%
“…AL relates to the situation where under repeated or chronic stress, the physiological homeostasis systems through the entire body become unbalanced and prone to developing diverse diseases. The concept of AL has been examined in bipolar disorder (Grande et al, 2012), major depressive disorder (Wilkinson and Goodyer, 2011) and schizophrenia (Nugent et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Allostatic load index provides a means to account for the systemic pathophysiological effects of cumulative stress exposure in psychiatric disorders. Previously, we found higher levels of allostatic load in patients with schizophrenia; and allostatic load was associated with worse functional capacity (Nugent et al, 2015). How elevated allostatic load may impact the brains of schizophrenia patients is unknown and is the focus on this study.…”
Section: Introductionmentioning
confidence: 85%
“…Blood pressure and heart rate was measured after at least 10 minutes of rest. Allostatic load data for 26 patients and 17 controls in this study were reported in a previous publication (Nugent et al, 2015). …”
Section: Methodsmentioning
confidence: 98%